Biomass accumulation response of cassava (Manihot esculenta C.) to NPK fertilization and biofertilizers in two soil types under greenhouse conditions (2018)
Cassava is one of the agricultural products of importance to food security in most developing countries. 50% of national production is concentrated in the Caribbean region, however, yields are low, as a consequence of the poor level of technification of the crop (MADR, 2006). The validation of practices associated with fertilization and the use of beneficial microorganisms is one of the alternatives to be included in the integrated management strategies of the crop.